The Relationship Between Cultural Food of Metuakan and Megibung with the Incidence of Hypertension at Karangasem I Health Center, Karangasem District, Bali, Indonesia - Luh Sri Anggayoni Julia Padmi; Komang Ayu Henny Achjar; I Ketut Gama; I Wayan Mustika; Agus Sri Lestari; Ketut Sudiantara; I Wayan Suardana; I Gusti Ketut Gede Ngurah (Knowledge Dynamics, 2025)
Background: Hypertension, a non-communicable disease, is defined by a systolic pressure of ≥ 140 mmHg and/or a diastolic pressure of ≥ 90 mmHg. Factors contributing to hypertension include alcohol consumption and diets high in salt and saturated fats. This study aims to explore the relationship between community cultural practices and the occurrence of hypertension. Methods: This study employed a quantitative correlational approach with a cross-sectional design. A probability sampling technique, specifically stratified random sampling, was used to select 90 participants who met the inclusion and exclusion criteria. Data analysis was conducted using the Spearman Rank correlation test. Results: The findings revealed that most respondents' cultural practices were categorized as poor (29 participants, 32.2%), followed by normal (17 participants, 18.9%), good (16 participants, 17.8%), very poor (15 participants, 16.7%), and very good (13 participants, 14.4%). Regarding hypertension severity, the majority of respondents experienced grade 1 hypertension (61 participants, 67.8%), while 29 participants (32.2%) had grade 2 hypertension. The study identified a significant relationship between community culture and hypertension incidence, with a p-value of 0.000. Conclusion: This study underscores the importance of increasing public awareness and educating hypertension patients about cultural practices that elevate the risk of hypertension, such as consuming alcohol and diets rich in salt and saturated fats.